Characterization of miRNAs in Extracellular Vesicles Released From Atlantic Salmon Monocyte-Like and Macrophage-Like Cells - Smith, Nicole C.; Wajnberg, Gabriel; Chacko, Simi; Woldemariam, Nardos T.; Lacroix, Jacynthe; Crapoulet, Nicolas; Ayre, D. Craig; Lewis, Stephen M.; Rise, Matthew L.; Andreassen, Rune; Christian, Sherri L. (Frontiers in Immunology, 2020)
Cell-derived extracellular vesicles (EVs) participate in cell-cell communication via transfer of molecular cargo including genetic material like miRNAs. In mammals, it has previously been established that EV-mediated transfer of miRNAs can alter the development or function of immune cells, such as macrophages. Our previous research revealed that Atlantic salmon head kidney leukocytes (HKLs) change their morphology, phagocytic ability and miRNA profile from primarily “monocyte-like” at Day 1to primarily “macrophage-like” at Day 5 of culture. Therefore, we aimed to characterize the miRNA cargo packaged in EVs released from these two cell populations. We successfully isolated EVs from Atlantic salmon HKL culture supernatants using the established Vn96 peptide-based pull-down. Isolation was validated using transmission electron microscopy, nanoparticle tracking analysis and Western blotting. RNA-sequencing identified 19 differentially enriched (DE) miRNAs packaged in Day 1 versus Day 5 EVs. Several of the highly abundant miRNAs, including those that were DE (e.g. ssa-miR-146a, ssa-miR-155 and ssa-miR-731), were also identified as DE in HKLs and are associated with macrophage differentiation and immune response in other species. Interestingly, the abundance of the miRNAs in EVs, including the most abundant miRNA (ssa-miR-125b), was different than the miRNA abundance in HKLs, indicating selective packaging of miRNAs in EVs. Further study of the miRNA cargo in EVs derived from fish immune cells will be an important next step in identifying EV biomarkers useful for evaluating immune cell function, fish health or response to disease.